(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This article analyzes the Ponta Grossa Legislation that to regulate the municipality’s activities designed to meet of the Coronavirus pandemic situation, focusing on epidemiological evolution and health security. From March 16 to June 30, 2020, 46 legal regulations were enacted by the municipality. The analysis considered that 16 of these regulations implemented strict measures for the ESD, 20 provided a softening of social distancing and 10 were palliative. The highest rate of social isolation in the city reached a weekly average of 51.76%, in March, however, until the last week of June this index fell 15.75%, reaching an average of 36.01%. The gradual reduction in social isolation is related to the softening of municipal legislation, which impacts on the growth of contaminated by COVID-19. The analysis reinforces that the public policies that target the ESD help to contain the increase in the number of contaminated and, thus, avoid the community quarantine.